A comparative genomic analysis of Xanthomonas arboricola pv. juglandis strains reveal hallmarks of mobile genetic elements in the adaptation and accelerated evolution of virulence - Assis, Renata A.B.; Varani, Alessandro M. [UNESP]; Sagawa, Cintia H.D.; Patané, José S.L.; Setubal, João Carlos; Uceda-Campos, Guillermo; da Silva, Aline Maria; Zaini, Paulo A.; Almeida, Nalvo F.; Moreira, Leandro Marcio; Dandekar, Abhaya M. (Elsevier, 2021)
Xanthomonas arboricola pv. juglandis (Xaj) is the most significant aboveground walnut bacterial pathogen. Disease management uses copper-based pesticides which induce pathogen resistance. We examined the genetic repertoire associated with adaptation and virulence evolution in Xaj. Comparative genomics of 32 Xaj strains reveal the possible acquisition and propagation of virulence factors via insertion sequences (IS). Fine-scale annotation revealed a Tn3 transposon (TnXaj417) encoding copper resistance genes acquired by horizontal gene transfer and associated with adaptation and tolerance to metal-based pesticides commonly used to manage pathogens in orchard ecosystems. Phylogenomic analysis reveals IS involvement in acquisition and diversification of type III effector proteins ranging from two to eight in non-pathogenic strains, 16 to 20 in pathogenic strains, besides six other putative effectors with a reduced identity degree found mostly among pathogenic strains. Yersiniabactin, xopK, xopAI, and antibiotic resistance genes are also located near ISs or inside genomic islands and structures resembling composite transposons.
Keywords: Copper resistance; Genome evolution; Lateral gene transfer; Mobile genetic elements; Replicative transposition; T3SS effectors